The Impact of Social Media on Students at the Bình Dương University - Cà Mau Campus - Tran , Thị Lan Anh; Nguyen, Văn Mạnh (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
This study focuses on analyzing the causes of social media's impact on students at the Bình Dương University - Cà Mau Campus. The research utilizes an online survey method with 102 participating students, thereby analyzing both subjective factors (awareness, attitude, motivation) and objective factors (social environment, living conditions) that influence social media usage behavior. The results indicate that students primarily use social media for communication and entertainment rather than for academic purposes. Additionally, excessive social media usage may lead to negative consequences such as decreased concentration, adverse effects on mental health, and reduced academic performance. The main objective is to clarify the positive and negative impacts of social media, particularly from popular platforms like Facebook, Zalo, Google, and YouTube, on students' habits and behaviors, thereby helping students use social media more effectively and maintain better balance in their lives.